Industrial 4.0 of Service and Manufacturing in Java-Indonesia: Level of Implementation - Dewi Nusraningrum; Salmi Mohd. Isa; Dipa Mulia (Universitas Mercu Buana, 2021)
The application of industry 4.0 has been doing in many countries in the world today even some developed countries have headed to industry 5.0, nevertheless in Indonesia there are still many companies that have not implemented industry 4.0. This research aims to find out the extent of the implementation of industry 4.0 in Indonesia, especially the industry located on the island of Java.The industry 4.0 aspects as a benchmark of differentiator from previous industrial developments is worth scrutinized to know its application levels in the service and manufacturing industries. Although many industries still combine their operating system between the 4.0 industry and conventional operating systems. The populations are the services and manufacturing companies. The data was obtained by using a questionnaire distributed online to respondents with a purposive sampling method. The data was grouped according to The level of implementation and is centered. The calculation and percentage results demonstrate that the level of implementation of the 4.0 industry with a technology base in service companies and manufacturing companies are at a managed level. It illustrates that the companies being researched have not been fully on the demands of the 4.0 industry.